The Effect of a Proposed Training Program on Some Elements of Physical Fitness among Students of the Athletics Training Course at Yarmouk University (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to identify the effect of a proposed training program on some elements of physical fitness among students of the athletics training course at Yarmouk University. The researchers used the experimental approach, and the study sample consisted of twenty (N= 20) students at Yarmouk University during the first semester of the academic year 2019-2020, who were purposively chosen. The samples were divided into two equal groups: experimental and control groups, with (10) students in each group. To analyze the results, means, standard deviation, Pearson correlation coefficient, paired samples t Test for double samples, and independent samples t Test were used. The results showed statistically significant differences related to the effect of the training program in relation to all study variables between the pre- and post- measurements of the two groups, in favor of the post measurement. The results further showed statistically significant differences among the post measurements in relation to all the study variables between the experimental and control groups in favor of the experimental group. The researchers recommended that the training program should be generalized to the athletics coaches in the Jordanian universities.
Keywords: Training Programmed Fitness Components; Athletics; Yarmouk University Students